Ovruch slate spindle whorls in the Czech Lands - Pavel Kouřil; Antonín Přichystal (Przegląd Archeologiczny)
The article discusses the state of knowledge and the significance of a special group of early medieval material culture artefacts – namely, spindle whorls made of Ovruch pyrophyllite slate originating from the territory of present-day Ukraine. Thousands of these artefacts, interesting not only for their specific, usually reddish color, but also for their professional standardized design, were made between the 10th and 13th c. Their occurrence in the Czech lands is very limited, however: only 13 specimens are presently known. In Bohemia, they have been discovered only in Prague, which was their target destination. In Moravia and Czech Silesia, they are known from five sites: with a single exception (a cemetery), they are important supra-regional and local fortified centers. Non-destructive analyses carried out have shown that all detected spindle whorls can be considered originals. An analysis of the archaeological contexts showed that the earliest occurrence of these imports can be dated as far back as the second half of the 10th century. However, most of them probably belong to the 11th century, and some, exceptionally, even to the 12th century. Given their low number, we assume that this most probably was not a regular item in long-distance trade.